Athar al-sihr fi al-mujtama' al-Kuwayti = Impact of the black magic upon Kuwait society / Naim Skenderi - Skenderi, Naim (2012)
The current study stands on one of the most important phenomena that threat the social stability in Kuwait which is the phenomenon of witchcraft, and its effects on the various categories of the society in this country. The research focuses on treating the issue of the spreading concerning the phenomenon of witchcraft and the causes of this spreading, its manifestations and its consequences on the social and economical aspects of life. Also, the current study stands on the direct impacts of this phenomenon through following the news in the newspapers and the statements of the security authorities. The research consists of three chapters; the first chapter introduces the definition of the phenomenon and the chosen country as a scope for the study. Whilst, the second chapter touches on the spreading faces of the phenomenon in Kuwaiti society, and the causes of that spreading, without neglecting the impacts of the religious beliefs in the circulation of this phenomenon. As well as, the second chapter touches on the negative socio-economical impacts on the society. While the third chapter takes care to consider how to facing the phenomenon of witchcraft and its effects, with the presentation of formal and informal efforts taken by authorities, also this chapter suggests solutions and proposals that would reduce this phenomenon as a prelude to eliminate it, and provides a part on the field survey study using questionnaires that attempt to answer several questions related to the subject.